2018
DOI: 10.1101/242941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CHC22 clathrin mediates traffic from early secretory compartments for human GLUT4 pathway biogenesis

Abstract: Glucose Transporter 4 (GLUT4) is sequestered inside muscle and fat, then released by vesicle traffic to the cell surface in response to post-prandial insulin for blood glucose clearance. Here we map the biogenesis of this GLUT4 traffic pathway in humans, which involves clathrin isoform CHC22. We observe that GLUT4 transits through the early secretory pathway more slowly than the constitutively-secreted GLUT1 transporter and localize CHC22 to the endoplasmic-reticulum-to-Golgi-intermediate compartment (ERGIC). … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 84 publications
5
50
0
Order By: Relevance
“…indicates that CHC22 enhances membrane traffic in an existing transport route for GLUT4 from the secretory pathway such that this route becomes more efficient for delivering GLUT4 to its insulin-responsive storage compartment and complements the established endocytic (30). Thus, we suggest that species with functional CHC22 clathrin are better at intracellular GLUT4 sequestration, resulting in lower surface GLUT4 in the absence of insulin, and tighter regulation of GLUT4 release in response to insulin.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…indicates that CHC22 enhances membrane traffic in an existing transport route for GLUT4 from the secretory pathway such that this route becomes more efficient for delivering GLUT4 to its insulin-responsive storage compartment and complements the established endocytic (30). Thus, we suggest that species with functional CHC22 clathrin are better at intracellular GLUT4 sequestration, resulting in lower surface GLUT4 in the absence of insulin, and tighter regulation of GLUT4 release in response to insulin.…”
Section: Discussionmentioning
confidence: 85%
“…Atypically for their epithelial cell origin but not for transformed cells, HeLa cells express CHC22 clathrin (they are homozygous for the M1316 variant) (28,29). We observed that the transfected fluorescently tagged CHC22 variants both localized similarly to endogenous CHC22-Met1316 (30). The dynamics of membrane association for the two allotypes was then tested.…”
Section: Chc22 Variants Display Functional Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the enriched immunoabsorption of cargo whose trafficking is specialized, but not constitutively recycling cargo, argues we are able to distinguish different regions or subdomains of the TGN. Interestingly, when GLUT4 is ectopically expressed in cell types that do not natively express GLUT4, such as fibroblasts, CHO cells, and HeLa cells, an insulin regulated recycling mechanism does exist, albeit less robust than in adipocytes (12, 60). Specifically, it has been demonstrated that GLUT4 travels to the PM in vesicles that are distinct from vesicles carrying constitutively recycling cargo (12).…”
Section: Discussionmentioning
confidence: 99%